Bilateral macular drusen in acquired partial lipodystrophy with type 2 membranoproliferative glomerulonephritis. Issue 6 (21st June 2021) - Tanner, Alexander; Chan, Hwei Wuen; Stears, Anna; Moosajee, Mariya
Abstract : A 35-year-old woman with acquired partial lipodystrophy (PLD) and features of type 2 membranoproliferative glomerulonephritis (MPGN-II), presented with difficulty in her fine detailed vision over the past year. She had right amblyopia from a hypermetropic anisometropia with astigmatism, displaying a best-corrected visual acuity of 0.50 and 0.00 LogMAR, in the right and left eye, respectively. Funduscopy showed bilateral symmetrical drusenoid deposits most prominent in the temporal macula with clusters in the superior and inferior retina, outside the temporal vascular arcades. Multimodal retinal imaging was performed, which confirmed hyperautofluorescent drusen located between the retinal pigment epithelium and Bruch's membrane. Electroretinography showed bilateral mild peripheral macular dysfunction, but normal central macular function on the pattern electroretinogram. Both PLD and macular drusen, are rare as distinct disease entities, but an association does exist and may be linked to MPGN-II.